Geochemistry at DSDP Legs 56-57 Holes - Sugisaki, Ryuichi (Supplement to: Sugisaki, R (1980): Major element chemistry of the Japan Trench sediments, Legs 56 and 57, Deep Sea Drilling Project. In: Scientific Party, Initial Reports of the Deep Sea Drilling Project, 56/57 (eds.), Initial Reports of the Deep Sea Drilling Project (U.S. Govt. Printing Office), 56-57, 1233-1249, https://doi.org/10.2973/dsdp.proc.5657.155.1980, 1980)
The bulk chemical composition of 257 argillaceous sediments from cores around the Japan Trench which were drilled during Legs 56 and 57 was determined and examined. These samples are generally enriched in SiO2 and impoverished in MnO, compared with typical pelagic sediments. SiO2 is negatively correlated with other oxides. Statistical treatment of data shows that pure silica varies inversely with TiO2 and Al2O3. The silica was derived mainly from planktonic siliceous organisms such as diatoms and radiolarians. Siliceous tests of these organisms disappear during progressive diagenesis, but the resolved silica redeposited in the sediments and the total silica content of the sediments remain constant. Higher SiO2 in some samples may be due to increased volcanic glass content. On the west slope of the trench, much ferric iron was deposited but not oxidized. In contrast to iron, manganese originally present in the sediments was apparently reduced and not precipitated in this hemipelagic region. Abundant land-derived organic materials maintain a weakly reducing environment within the sediment, which permits the precipitation of ferric iron but not of manganese. The mutual relationship of conservative elements such as SiO2, TiO2, and Al2O3 indicates that sediments of the west slope of the trench were derived mostly from the land area to the west and that the original materials were chemically homogenized and diluted by biogenic silica. In contrast, the chemistry of core from the trench outer slope (Site 436) shows a vertical trend: SiO2 progressively decreases downhole, whereas MnO and the Fe2O3/FeO ratio increase significantly. The deeper samples are very similar to the pelagic sediments from the Pacific Plate, whereas upper samples resemble the trench inner slope sediments. The vertical trends at this site are plausibly explained by the progressive movement of the ocean plate toward the Japan Trench. When the oceanic plate was in the Central Pacific Ocean, much MnO and Fe2O3 were deposited under an oxidizing environment with slow sedimentation, owing to the paucity of organic materials. As the ocean plate moved westward, nearer to the Japanese Islands, hemipelagic sediment derived from these islands were deposited over the pelagic sediments. No pelagic sediments were detected geochemically in the deposits of the trench inner slope. If the offscraping of the sediment of the oceanic plate is the dominant process at the plate convergence, significant amounts of deep oceanic pelagic sediments that are being scraped off from the oceanic plate should be contained in the trench inner slope. Since the pelagic sediments are known to exist on oceanic crust coming into the trench, it may be that the pelagic sediments are subducted without offscraping against the landward wall of the trench. However, the entire sequence underlying the trench inner slope was not penetrated at any site.